PEGUAM SYAR’I: AMALAN DAN KEDUDUKANNYA DI MALAYSIA - Mohamed Adil, Mohamed Azam (Jurnal Syariah, 2019)
The discussion on the engagement of shar' i lawyers is focused on the method and regulation as instituted by various states of Malaysia. It is suggested that Shar'i lawyers graduated from the Shariah schools of laws be given opportunities to represent their clients in Civil Courts. A number of suggestions are made of how to enhance the efficiency and experiences of those lawyers so as to be more effective in assisting judges in Shariah Courts in upholding justice as required by the Shariat.